Reflections on the ESRC internship scheme for postgraduates. Issue 1 (2nd January 2017) - Bos, Daniel; Finlay, Robin; Hopkins, Peter; Lloyd, Jenny; Richardson, Michael
Abstract: The Economic and Social Research Council (ESRC) in the UK is one of the main sources of funding for postgraduate study in human geography. For some years now, the ESRC has offered funded students the opportunity to apply to undertake a short internship in a government department or with a Non-Governmental Organization (NGO). This paper provides a collective reflection from the perspective of four former postgraduates who completed different ESRC supported internships in the UK. We discuss the enhancement of writing skills for diverse audiences, the advancement of knowledge in diverse subject areas, and the opening up of employment opportunities as key benefits of participating in the ESRC internship scheme.